Intriguingly tuning the fluorescence of AIEgen using responsive polyelectrolyte microspheres. Issue 109 (11th November 2016) - Guan, Xiaolin; Zhang, Donghai; Jia, Tianming; Zhang, Yang; Meng, Li; Jin, Qijun; Ma, Hengchang; Lu, Dedai; Lai, Shoujun; Lei, Ziqiang
Abstract : We successfully synthesized counterion-sensitive TPE–METAC polyelectrolyte microspheres and tuned its fluorescence and size by ClO4 −, PF6 − and TFSI − . Abstract : In this study, we present a practical approach to tune the fluorescence of AIEgen (the luminogens exhibiting AIE attributes) based on counterion-sensitive polyelectrolyte microspheres. The tunable fluorescence is induced by counterion-driven interactions in polyelectrolyte microspheres by a simple exchange of the counterions. The effects of different types of opposite counterions on the fluorescent properties of a new polyelectrolyte tetraphenylethene- graft -poly[2-(methacryloyloxy)-ethyltrimethylammonium chloride] (TPE–PMETAC), which was synthesized by Atom Transfer Radical Polymerization (ATRP) using a TPE derivative containing four arms as an initiator, were systematically investigated. For cationic microspheres with quaternary ammonium groups, the fluorescence intensity progressively increased according to the counterion series Cl − < ClO4 − < PF6 − < TFSI −, which is in accord with the ability of exchanged hydrophilic Cl − by hydrophobic anions in the order of ClO4 − < PF6 − < TFSI − . The mechanism of tuning fluorescence was determined by dynamic light scattering (DLS), zeta-potentials and scanning electron microscopy (SEM). We proved that the size of the microspheres and electrostatic repulsive forces between the microspheres were decreased by the addition of counterions due to the hydrophobic-induced collapse of the surfaces of the microspheres. As a result, the obvious increase in the fluorescence of AIEgen was obtained based on the aggregation of microspheres.